Gallus gallus domesticus are resistant to infection with Neospora caninum tachyzoites of the NC-1 strain - Munhoz, Alexandre Dias; Amaral, Tatiane Fernanda do [UNESP]; Goncalves, Luiz Ricardo [UNESP]; Barbosa de Moraes, Vera Maria [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier B.V., 2014)
The aim of this study was to experimentally evaluate infection in Gallus gallus domesticus with Neospora caninum tachyzoites of the NC-1 strain. Experimental infection was conducted in 90-day-old chickens, embryonated eggs and bioassays in dogs. In the first experiment, poults were randomly divided into four groups. Groups I and II were provided feed with coccidiostat, whereas groups III and IV received feed without coccidiostat. When the poults from groups I and III reached 90 days of age, they received a subcutaneous inoculation of N. caninum. Once the hens entered their egg-laying period, during the following 30 days, the eggs were collected, identified, weighed and placed in an incubator. On the 70th day after inoculation, all animals, including the chicks, were euthanized. Tissue samples from the adult poultry and chicks were collected for histopathology, immunohistochemistry (IHC) and PCR. Brain tissue and pectoral muscle samples from infected birds were fed to two dogs. Notably, the average weight of the group III eggs was lower than that of the group IV eggs (p <0.05). No changes consistent with infection in adult poultry or chicks were detected by histopathology or IHC; moreover, no amplified parasite DNA was detected in the birds'tissues or dogs'feces. No dog eliminated oocysts. In the second experiment, the embryonated chicken eggs were inoculated with 1 x 10(2) N. caninum tachyzoites, on the 10th day of incubation, and chicks born from these eggs were housed in boxes suitable for the species and received commercial feed and distilled water ad libitum. On the 30th day after infection (DAI), the poultry were euthanized, and their organs were processed as described in experiment I. The amplification of parasite DNA was observed in the spleen and pectoral muscles of one of the birds. The ingestion of bird tissues by dogs did not result in oocyst elimination. These results indicate that the parasite may have been eliminated by the host and that the use of tachyzoites to induce chronic disease might be a poor source for hens. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Neosporosis; Poultry; Resistance; DNA; PCR